Effect of cyclosporin A on respiratory viral replication in fully differentiated ex vivo human airway epithelia - Louise Bondeelle; Song Huang; Samuel Constant; Sophie Clément; Maud Salmona; Jérôme Le Goff; Anne Bergeron; Caroline Tapparel (Wiley, 2024)
Abstract Cyclosporin A (CsA), an immunosuppressive drug used in transplant recipients, inhibits graft rejection by binding to cyclophilins and competitively inhibiting calcineurin. While concerns about respiratory infections in immunosuppressed patients exist, contradictory data emerged during the COVID‐19 pandemic, prompting investigations into CsA's impact on viral infections. This study explores CsA's antiviral effects on SARS‐CoV‐2 Omicron BA.1, Delta variants, and human parainfluenza virus 3 (HPIV3) using an ex vivo model of human airway epithelium (HAE). CsA exhibited a dose‐dependent antiviral effect against the SARS‐CoV‐2 Delta variant, reducing viral load over 10 days. However, no significant impact was observed against SARS‐CoV‐2 Omicron or HPIV3, indicating a virus‐specific effect. At high concentrations, CsA was associated with an increase of IL‐8 and a decrease of IFNλ expression in infected and noninfected HAE. This study highlights the complexity of CsA's antiviral mechanisms, more likely involving intricate inflammatory pathways and interactions with specific viral proteins. The research provides novel insights into CsA's effects on respiratory viruses, emphasizing the need for understanding drug-virus interactions in optimizing therapeutic approaches for transplant recipients and advancing knowledge on immunosuppressive treatments' implications on respiratory viral infections. Limitations include the model's inability to assess T lymphocyte activation, suggesting the necessity for further comprehensive studies to decipher the intricate dynamics of immunosuppressive treatments on respiratory viral infections.